The Barristers of Toulouse in the Eighteenth Century (1740-1793) - Berlanstein, Lenard (Johns Hopkins University Press, 2022)
Originally published in 1975. Following the vein of French historiography, many twentieth-century scholars of the French Revolution believed that the middle class of lawyers played a crucial role in the Revolution. In The Barristers of Toulouse, Lenard Berlanstein contends with that notion in a case study examining the response of the Toulousian legal community to the French Revolution. Using tax rolls, marriage contracts, and court records as primary sources, Professor Berlanstein argues that class interests—such as a desire to preserve their status in the cultured, conservative urban elite—led many Toulousian judges and lawyers to reject the Revolution and to remain loyal to the aristocratic Parlement. In other words, those in the legal community of Toulouse conducted themselves in ways that were consistent with other members of their social and economic class. To supplement his argument, Berlanstein's integrates methods from the New Social History movement.